French-Spanish Translation of Proper Names of Characters in two texts of Children’s Literature - Lobato Patricio, Julia (2022)
Abstract This research analyses the problems of translating proper names in two French texts of children's literature: Jefferson and La Fée Électricité. The aim is to put forward proposals for the translation into Spanish of proper names referring to historical and fictional characters based on the strategies and techniques of Mayoral and Muñoz (1997) and Hurtado (2001). For this purpose, the state of the art on children's literature and rhetorical resources are analysed; subsequently, the concept of proper names is explained and the case studies, the strategies and techniques adopted for each of them as well as the proposed solutions for the examples extracted are described. From this, the research concludes that proper names constitute a real translation problem for which different solutions have been proposed according to their nature.